Modulation Of Galactic Cosmic Rays Due To Magnetic Clouds And Associated Structures In The Interplanetary Space: 1996-2018 - Fadaaq, M.; Badruddin, B. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
We study the modulation of galactic cosmic rays due to magnetic clouds observed during solar cycles 23 and 24 (1996-2018). We utilize solar wind plasma and field data together with cosmic ray intensity (CRI) data during the passage of magnetic clouds and associated structures. We apply superposed epoch analysis to analyze these data. We study the relative importance of magnetic clouds and their associated structures in modulating the cosmic rays. We observe significant differences in the amplitudes and time profiles of transient depressions in cosmic ray intensity due to magnetic regimes of different field strengths and topologies. We discuss the observed results in light of differences in the simultaneous plasma and magnetic field properties. Исследована модуляция галактических космических лучей магнитными облаками, наблюдаемых во время 23 и 24 солнечных циклов (1996-2018гг.). Использованы данные о плазме и поле солнечного ветра вместе с данными об интенсивности космических лучей во время прохождения магнитных облаков и связанных с ними структур. Применен "наложенный анализ эпох" (superposed epoch analysis) для анализа этих данных. Мы исследовали относительную важность магнитных облаков и связанных с ними структур в модуляции космических лучей. Обнаружены значительные различия в амплитудах и временных профилях транзиентных депрессий в интенсивности космических лучей из-за магнитных режимов при различных напряженностях поля и топологии. Наблюдаемые результаты обсуждены в свете различий в одновременных свойствах плазмы и магнитного поля.
Keywords: Astrophysics